The Influence of Service Quality and Security on Customer Loyalty Through Customer Satisfaction (a case at Lalamove) - Marthaleina Ruminda; Veronica Veronica; Arya Maulana Azitama (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The purpose of this study is to determine the effect of service quality, and security on customer loyalty with customer satisfaction as a mediation tool. In this study, questionnaires are used to collect data focused on Lalamove users in DKI Jakarta using quantitative approaches. A basic random sampling procedure is used to acquire a sample of 133 respondents. Samples were obtained using purposive sampling techniques and data analysis using Structural Equation Modelling (SEM). The independent variables used are service quality and security, and the dependent variables are customer loyalty and customer satisfaction as intervening variables. This demonstrates that through consumer pleasure, there is a noteworthy and positive association among the independent variables of service quality and security and customer loyalty as variables dependent. This research revealed that customer satisfaction exerts a substantial positive influence on customer loyalty, emphasizing that contented customers are more inclined to maintain their loyalty to the company.